2016
DOI: 10.1103/physrevc.93.055204
|View full text |Cite
|
Sign up to set email alerts
|

Bubble dynamics and the quark-hadron phase transition in nuclear collisions

Abstract: We study the nucleation of a quark gluon plasma (QGP) phase in a hadron gas at low temperatures and high baryon densities. This kind of process will presumably happen very often in nuclear collisions at FAIR and NICA. When the appropriate energy densities (or baryon densities) and temperatures are reached the conversion of one phase into another is not instantaneous. It is a complex process, which involves the nucleation of bubbles of the new phase. One important element of this transition process is the rate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For the dynamic processes where the transition between SQM and hadronic matter takes place, the interface effects also play important roles. For example, it was shown that a larger σ inhibits quark matter nucleation during the deconfinement phase transitions in cold neutron stars [55,56], core-collapse supernova [57,58], and heavy-ion collisions [59,60]. Similarly, the interface effects are important for the hadronization phase transition in the early Universe [61,62,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…For the dynamic processes where the transition between SQM and hadronic matter takes place, the interface effects also play important roles. For example, it was shown that a larger σ inhibits quark matter nucleation during the deconfinement phase transitions in cold neutron stars [55,56], core-collapse supernova [57,58], and heavy-ion collisions [59,60]. Similarly, the interface effects are important for the hadronization phase transition in the early Universe [61,62,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…The transition between SQM and HM is also sensitive to the interface effects. For the creation of SQM in neutron stars [46,47], core-collapse supernova [48,49], and heavy-ion collisions [50,51], it was show that the surface tension plays a crucial role, where larger σ disfavors or inhibits quark matter nucleation in HM. The survival of SQM objects in a heated environment is also sensitive to the value of σ, where SQM objects may not have survived the evaporation or boiling process in the early Universe [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%